Low Vitamin D Status and Suicide: A Case-Control Study of Active Duty Military Service Members - Umhau, John C.; George, David T.; Heaney, Robert P.; Lewis, Michael D.; Ursano, Robert J.; Heilig, Markus; Hibbeln, Joseph R.; Schwandt, Melanie L. (PloS one, 2013)
Considering that epidemiological studies show that suicide rates in many countries are highest in the spring when vitamin D status is lowest, and that low vitamin D status can affect brain function, we sought to evaluate if a low level of 25-hydroxyvitamin D [25(OH)D] could be a predisposing factor for suicide. We conducted a prospective, nested, case-control study using serum samples stored in the Department of Defense Serum Repository. Participants were previously deployed active duty US military personnel (2002-2008) who had a recent archived serum sample available for analysis. Vitamin D status was estimated by measuring 25(OH) D levels in serum samples drawn within 24 months of the suicide. Each verified suicide case (n = 495) was matched to a control (n = 495) by rank, age and sex. We calculated odds ratio of suicide associated with categorical levels (octiles) of 25(OH) D, adjusted by season of serum collection. More than 30% of all subjects had 25(OH)D values below 20 ng/mL. Although mean serum 25(OH)D concentrations did not differ between suicide cases and controls, risk estimates indicated that subjects in the lowest octile of season-adjusted 25(OH)D (<15.5 ng/mL) had the highest risk of suicide, with subjects in the subsequent higher octiles showing approximately the same level of decreased risk (combined odds ratio compared to lowest octile = 0.49; 95% C.I.: 0.315-0.768). Low vitamin D status is common in active duty service members. The lowest 25(OH)D levels are associated with an increased risk for suicide. Future studies could determine if additional sunlight exposure and vitamin D supplementation might reduce suicide by increasing 25(OH) D levels.